Impact of COVID-19 Pandemic on Mental Health and Personality Traits. A Conceptual Review - Koutsioumpa, Eftichia Maria (Technium Social Sciences Journal, 2023)
Introduction: The COVID-19 epidemic has substantially impacted humans’ physical and emotional well-being. The epidemic elicits diverse responses from individuals, which can be attributed to various facets of their personality. Objective: This study aims to examine the impact of the COVID-19 pandemic on individuals’ mental health while also exploring the potential mediating role of personality factors in this relationship. Methods: The methodology employed in this study was the execution of a systematic literature review, which encompassed the examination of research papers published throughout the timeframe of 2020-2021. Following a rigorous evaluation process based on predetermined inclusion criteria, 12 publications were deemed suitable for the analysis. Findings: The study’s findings are as follows: Concerning personality constructs, it was shown that neuroticism, narcissism, and maladjustment exhibited a positive correlation with symptoms of depression and anxiety. In contrast, a negative correlation exists between certain good personality traits, namely conscientiousness, receptivity to new experiences, emotional stability, adaptability, and resilience, and symptoms associated with anxiety, depression, and other mental disorders. Extroversion has been identified as a potential risk factor for the manifestation of the symptoms mentioned above in specific investigations. However, other studies have found it to serve as a protective factor. Conclusion: In light of the scarcity of available literature, it is justifiable to assert that personality can serve as a dual mediator, exerting positive and negative influences on the association between COVID-19 and individuals’ mental well-being.